Second Language Socialization in a Bilingual Chat Room: Global and Local Considerations - Wan Shun Eva Lam (Language Learning and Technology)
This paper considers how global practices of English on the Internet intersect with local practices of English in the territorial or national sphere in constructing the language experiences of immigrant learners. Using a multi-contextual approach to language socialization, this paper examines the social and discursive practices in a Chinese/English bilingual chat room and how this Internet chat room provides an additional context of language socialization for two teenage Chinese immigrants in the US. Analysis of discourse, interview, and observational data reveals that a mixed-code variety of English is adopted and developed among the focal youth and their peers around the globe to construct their relationships as bilingual speakers of English and Cantonese. This language variety served to create a collective ethnic identity for these young people and allowed the girls to assume a new identity in speaking English that doesn't follow the social categories of English-speaking Americans versus Cantonese-speaking Chinese in their local American context. This paper makes the case for studying how people navigate across contexts of socialization in the locality of the nation-state and the virtual environments of the Internet to articulate new ways of using English.